A COMPARATIVE STUDY BETWEEN JOINT MOBILIZATION AND CONVENTIONAL PHYSIOTHERAPY IN KNEE OSTEOARTHRITIS (International Journal of Physiotherapy, 2016)
Background: Osteoarthritis (O.A.) is an active disease process involving articular cartilage destruction, subchondral bone thickening and new bone formation. Worldwide osteoarthritis is estimated to be the fourth leading cause of disability, in which 10% are males and 13% are females. Studies from china, Bangladesh and Pakistan have shown high prevalence of knee osteoarthritis. Pharmacological interventions, surgical procedures and Physiotherapy management play important role in knee Osteoarthritis. In Physiotherapy management of osteoarthritis, manual therapy along with thermotherapy and/or electrotherapy is used. Current study was to evaluate the effectiveness of joint mobilization in knee osteo-arthritis.Methods: Comparative study was undertaken on 50 patients with osteoarthritis of the knee who were randomly assigned to one of two groups that received Joint mobilization alone (n = 25; mean age, 53 years) or Conventional Physiotherapy (n = 25; mean age, 50 years).Both groups were received their programs for 8 weeks; two sessions per week. Analysis of data within group and between groups of the pre and post treatment values of the function and pain was done using pair t test and independent t test.Results: Both groups showed significant improvement in ISOA score and VAS. There was statistical significant difference between the two groups (Group A and B) i.e. p < 0.005.Conclusion: Manual joint mobilization improves the effectiveness of the treatment program in treating symptoms of knee OA and improves function in elderly people with knee OA.